Pir sensor based security system - Sanikommu Umamaheswari (Annals of Robotics and Automation - Peertechz Publications, 2020)
In this paper passive Infrared sensor "PIR" based security system is introduced. With this sensor we can save power, and effective management at low cost and requires small memory space. The PIR sensor is responsible for detecting the change in infrared radiation levels when an intruder or human is passed through the system or space where it is arranged. Depending on the change in radiation levels the change in voltages occurs and then with this voltage the signal is amplified and hence the sound will be produced. Thus it is helpful in various applications and areas . This type of system has many advantages compared to the existing system.